MOPA pulsed fiber laser for silicon scribing - Yang, Limei; Huang, Wei; Deng, Mengmeng; Li, Feng (Optics and laser technology, 2016)
A 1064nm master oscillator power amplifier (MOPA) pulsed fiber laser is developed with flexible control over the pulse width, repetition frequency and peak power, and it is used to investigate the dependence of mono-crystalline silicon scribe depth on the laser pulse width, scanning speed and repeat times. Experimental results indicate that long pulses with low peak powers lead to deep ablation depths. We also demonstrate that the ablation depth grows fast with the scanning repeat times at first and progressively tends to be saturated when the repeat times reach a certain level. A thermal model considering the laser pulse overlapping effect that predicts the silicon temperature variation and scribe depth is employed to verify the experimental conclusions with reasonably close agreement. These conclusions are of great benefits to the optimization of the laser material processing with high efficiency. •A 1064nm MOPA pulsed fiber laser with flexible parameters was developed.•A thermal model considering the laser pulse overlapping effect was built.•We investigate the dependence of silicon scribe depth on system parameters.•The ablation depth progressively saturates with the increasing of repeat times.•The work is of great value to the optimization of MOPA laser material processing.